A Framework For Overcoming M-commerce Adoption Barriers In Angola - Tengeh, Robertson Khan; Justino , Mateus Vicente; Twum-Darko, Michael (Journal of Economic Development, Environment and People, 2023)
Abstract. The COVID-19 pandemic has significantly impacted the global economy, with brick-and-mortar businesses particularly hard-hit. In Angola, the lockdown imposed in response to the pandemic forced many companies to close their doors, leading to widespread job losses and economic hardship. However, the pandemic also presented an opportunity for businesses that could adopt m-commerce or other alternative sales channels. This study aims to understand the factors that have impeded the adoption of m-commerce by brick-and-mortar retail SMEs in Angola during the COVID-19 pandemic. The study also proposes a conceptual framework for overcoming the m-commerce adoption barriers that these SMEs have encountered. The study was conducted using a mixed-method approach, with data collected from 306 retail business managers/owners and professionals through a structured questionnaire and semi-structured interviews. The study’s findings suggest that the factors impeding m-commerce adoption were the lack of experience in using m-commerce, skills to configure forward and backward distribution systems, personnel with IT skills; the cost of m-commerce infrastructure; and the lack of support from the external environment. The study concludes by proposing a framework/strategy for stimulating the adoption of m-commerce in Angola. This strategy includes providing training and support to businesses on using m-commerce, developing a supportive regulatory environment, and investing in m-commerce infrastructure.